We have to reflect each point of the triangles over the x-axis.
We can start by finding the algebraic expression for the rule for this type of reflection.
For any given point (x,y), when reflected across the x-axis, it will keep its x-coordinate but its y-coordinate will change sign.
Then, we can express this as a rule like:
![\lparen x,y)-->\left(x,-y\right)](https://img.qammunity.org/2023/formulas/mathematics/college/m1a4i3frmpoing1df53wect7ihwzavwms0.png)
Then, we can apply this rule for each of the points as:
![\begin{gathered} J\left(-7,-7\right)-->J^(\prime)\left(-7,7\right) \\ K\left(-5,-2\right)-->K^(\prime)\left(-5,2\right) \\ L\left(-2,-3\right)-->L\left(-2,3\right) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xo0tav85lbj47xecf63w83gir3ltqkpb8s.png)
Answer:
J' = (-7, 7), K' = (-5, 2), L' = (-2, 3).
The algebraic expression is (x, y) --> (x, −y).